Enhancement of temperature measurement in nuclear power plants - Pytel, Ivan; Borukh, Roman (Видавництво Національного університету “Львівська політехніка”, 2024)
One of the most critical challenges in nuclear power is reliably determining the temperature state of fuel assemblies. Successful resolution of this problem affects the possibilities for enhancing a nuclear reactor’s reliability, efficiency, and service life. This paper analyzes methods for detecting the contact of the thermocouple in the reactor cassette head for temperature measurement.
Keywords: Thermocouple with a protective shell; Time constant; Measurement accuracy; and Optimization of placement